The Need to Focus on Therapy Instead of Associations - Reid, Gregor (Frontiers in Cellular and Infection Microbiology, 2019)
Molecular analyses of the vaginal microbiota have uncovered a vast array of organisms in this niche, but not so far changed what has been known for a long time: lactobacilli are dominant in health, and the diagnosis and treatment of symptomatic bacterial vaginosis is sub-optimal and has not changed for over forty years. While the lowering cost of DNA sequencing has attracted more researchers to the field, and bioinformatic and statistical tools have made it possible to produce large datasets, it is functional and actionable studies that are more urgently needed, not more microbial abundance and health or disease-associative data. The triggers of dysbiosis remain to be identified, but ultimately treatment will require disrupting biofilms of primarily anaerobic bacteria and replacing them with the host’s own lactobacilli or health-promoting organisms. The options of using probiotic strains to displace the biofilms and for prebiotics to encourage resurgence of the indigenous lactobacilli hold great promise, but more researchers need to develop and test these concepts in humans. The enormity of the problem of vaginal dysbiosis cannot be understated. It should not take another forty years to offer better management options.